Change of body balance in dancers during two years training - Tomaszewski, Paweł; Szulc, Adam; Buśko, Krzysztof (Journal of Education, Health and Sport, 2017)
Celem pracy była ocena równowagi ciała osób uprawiających taniec po dwóch latach treningu. W badaniach uczestniczyło 16 tancerzy zespołu pieśni i tańca Ziemia Bydgoska. W celu oceny równowagi ciała wykonano dwukrotnie dwa testy stabilometryczne (oczy otwarte, oczy zamknięte) na platformie stabilometrycznej Sigma w odstępie dwóch lat. Mierzono zmiany położenia COP (Center of Pressure). Testy z oczami otwartymi i z oczami zamkniętymi wypadły zdecydowanie lepiej w pierwszym pomiarze w porównaniu z pomiarem II wykonanym po dwóch latach. Większe różnice wszystkich parametrów obserwowano w teście oczy otwarte w porównaniu z testem oczy zamknięte po upływie dwóch lat. Na podstawie uzyskanych wyników można stwierdzić, że po dwuletnim cyklu uprawiania tańca zdolności do utrzymania równowagi ciała uległy pogorszeniu. Abstract The purpose of the study was to evaluate the body balance in persons who practice the dance during two years of training. The study involved 16 dancers of Bydgoszcz’s song and dance team. In order to assess body balance, two stabilometric tests (eyes open, eyes closed) were performed on a Sigma stabilometer platform at intervals of two-years. Change of sways of the Centre of Pressure (COP) was measured during 30 second. Tests with open eyes and closed eyes were significantly better in the first measurement compared to the second measurement after two years. More differences were observed in the test eyes open compared to test eyes closed after two years. Based on the obtained results it can be stated that after two years of dance practice the ability to maintain balance of body has deteriorated.